Influência do trauma dentoalveolar e do tipo de força ortodôntica sobre o complexo dentinopulpar - estudo experimental em ratos - Castilhos, Jussimar Scheffer (2020)
The present study aims to analyze the amount of tooth movement and pulp conditions in teeth with dentoalveolar trauma history (extrusive luxation), when three types of orthodontic forces are applied. For this, 48 Wistar rats were divided into 8 groups (n = 6), having as variables the three different types of orthodontic forces: continuous (FC), interrupted continuous (FCI) and intermitent (FI), the presence or absence of trauma (CT or ST) and the presence or not orthodontic movement (CM or SM). The groups were arranged as follows: STFC, STFCI, STFI, CTFC, CTFCI, CTFI, CTSM and STSM (control group). Extrusive dislocation (LE) of the healthy upper right first molar was performed and after 15 days for periodontal reestablishment, the orthodontic springs were installed as devices to promote induced tooth movement and on the 14th day after the first activation, the amount of tooth movement was measured and euthanasia of the animals was performed for mounting the histological slides and histomorphometric evaluation. The variables analyzed were divided into 4 major groups: cellularity pattern, dystrophic alterations, hemodynamic alterations and dentin alterations. The obtained data were statistically examined by an appropriate test according to the characteristic of each variable. The results showed that there was a statistically significant difference in tooth movement for FC and FCI forces compared with FI (p <0.05). There was a lower amount of inflammatory infiltrate in the control group compared with others. The FC showed higher resorption area. Pulp changes are more frequent in relation to hemodynamic alterations, followed by dentin alterations, cellularity alterations, and lastly, dystrophic alterations, but without difference among the groups.